Biochemical Adaptations to Prolonged Starvation in Freshwater Catfish: Gonadal Glycogen Dynamics - Sahani, Suresh Kumar; Prasad, Nayan K.; Shachi, Kumari (Formosa Journal of Multidisciplinary Research, 2024)
Starvation significantly impacts fish species, affecting various organs. This study examines the effect of prolonged starvation on glycogen content in the gonadal tissue of Clarias batrachus, a freshwater catfish. Using a calorimetric method, glycogen levels in gonadal tissues were measured over a 40-day period at 10-day intervals. Results showed a gradual decline in glycogen content, likely due to increased gluconeogenesis and heightened rates of deamination. Male specimens exhibited a more pronounced glycogen depletion compared to females. Initially, the reduction was minimal up to 20 days, followed by a sharp decline, resulting in an 80% reduction by day 40. These findings highlight significant metabolic adaptations in Clarias batrachus during prolonged starvation.